Pendampingan Legalitas Usaha Melalui Pengurusan NIB di Desa Kemiri, Kecamatan Puspo, Pasuruan - Anindya Calista Mayang; Farrel Athala Ramadhana; Gita Aurellia Vanya; Dita Atasa (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Business legality through the ownership of a Business Identification Number (NIB) is an essential prerequisite for MSME and BUMDes actors to gain access to government support, financing, and professional business development. However, in Kemiri Village, Puspo Subdistrict, Pasuruan Regency, the level of understanding and ownership of the NIB remains very low due to limited legal literacy and access to information. This community service activity aims to enhance public awareness, knowledge, and skills in managing NIB as a form of business legality. The targets of this business legality assistance activity are MSME actors in Kemiri Village and the village officials themselves. The methods used include socialization, surveys, demonstrations, and direct technical assistance to MSME actors and BUMDes managers. The results of the activity show a significant increase in participants' understanding of the functions, benefits, and procedures for obtaining an NIB, demonstrated by a 64% increase in pre-test and post-test scores. All assisted participants successfully obtained NIBs, both for individual micro businesses and village institutions. The issuance of the NIB strengthens the legal standing of business actors, opens access to government programs, and encourages sustainable village economic development. The NIB assistance program has proven effective as an empowerment strategy based on legality and local potential.